Memanfaatkan Multimedia Sebagai Sarana Pendidikan Islami Pada Era Digitalisasi Di SDN 09 Panai Tengah - Mila Rosdiana Sianipar (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Based on IDM data (Development Village Index) Panai Tengah sub-district which is part of Labuhan Batu Regency is categorized as a disadvantaged area. This is the reason for carrying out research at that location. It was found that the availability of multimedia at the school was only 1, so that schools did not make use of multimedia in their learning activities. In this case, the author's goal of using multimedia in teaching activities is to help students understand the subject matter because they can feel both audio and visual simultaneously by looking at the screens displayed at school. Another goal to be achieved is to find out the response of students regarding the teaching activities that have been carried out. The problem experienced by schools is the lack of utilization of multimedia in teaching, even though currently technology has experienced rapid progress and needs to be pursued, including in teaching activities so that teaching activities using multimedia are made by the author in the hope that the implementation of teaching activities will not be monotonous in lecture activities. With the use of multimedia, students can express their understanding from the video that is broadcast freely as they can understand from the video. The results obtained from teaching activities are that students can easily understand the material presented because besides seeing directly they can also hear the display presented on the screen. In addition, they enthusiastically participated in teaching activities because the duration of the videos played was not long so students did not feel bored with teaching activities. Keywords: multimedia; means; digitization.